Mesalazine: a novel therapeutic agent for periodontitis via regulation of periodontal microbiota and inhibiting Porphyromonas gingivalis - Wang, Yuqi; Ma, Jun; Wang, Haoyu; Yi, Jingzheng; Bai, Yuxin; Hu, Min; Yan, Jiaqing (Frontiers in Microbiology, 2025)
IntroductionPeriodontitis and inflammatory bowel disease are chronic inflammatory diseases with shared epidemiological, biological, and therapeutic associations. Given the similarities in their pathogenic factors, this study hypothesized that mesalazine, a key treatment agent for inflammatory bowel disease, could also be effective in managing periodontitis.MethodsThe antimicrobial effect of mesalazine on Porphyromonas gingivalis was investigated in vitro, including observations of morphological changes on the surface of P. gingivalis. Additionally, the impact of mesalazine on both the formation and established plaque biofilms was examined. The antimicrobial mechanism was elucidated by assessing the expression of P. gingivalis virulence genes and by determining the disruptive effect on P. gingivalis cell membranes. An in vivo rat model of periodontitis was constructed to evaluate mesalazine’s efficacy and its influence on the periodontal bacterial flora in the context of periodontitis.Results and discussionOur results demonstrated that mesalazine concentrations ranging from 0.5 to 2 mg/mL significantly inhibited P. gingivalis proliferation over 72 h. Flow cytometry revealed a marked reduction in the number of viable cells following mesalazine treatment. At the nanometer scale, mesalazine induced crumpling and rupture of the P. gingivalis surface, compromising cell membrane integrity. Mesalazine not only suppressed the formation of plaque biofilms by P. gingivalis and polymicrobial communities but also disrupted pre-existing biofilms. The data also suggested that mesalazine could disrupt the integrity of the P. gingivalis cell membrane and inhibit the expression of virulence factors. An animal model of periodontitis in rats was successfully constructed in vivo. Mesalazine treatment inhibited alveolar bone resorption, alleviated inflammation of periodontal tissues, and improved the composition of the periodontal flora to a healthier state. This study establishes that mesalazine can treat periodontitis through modulation of the periodontal flora and its anti-inflammatory properties, thus broadening its classical therapeutic applications.